2022
DOI: 10.5829/ije.2022.35.07a.10
|View full text |Cite
|
Sign up to set email alerts
|

Response of Rubcrete Continuous Deep Beams under Sinusoidal Loads

Abstract: Continuous deep beams (CDBs) are the most used members in constructions with highly exposing to different types of dynamic loads. It is well known that; the concrete is a brittle material and has a weak resistance to energy absorption. Using scrapped tire rubber enhances the concrete energy absorption for sustainability purposes. Timoshenko beam theory has been used to solve CDBs subjected to sinusoidal load and has been adopted for verification of numerical results of ANSYS APDL V.15.0. Seven concrete mixes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…They analytically studied the effect of a moving harmonic load on beams with different boundary conditions. Several parameters had been thought out, such as the type of support, excitation frequency, and speed of the harmonic load [15][16][17]. Minh et al [16] studied experimentally the vibration characteristics of cantilever sandwich beams and panels under the harmonic force applied at the free edge based on the response history of the accelerometer signal and displacement signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They analytically studied the effect of a moving harmonic load on beams with different boundary conditions. Several parameters had been thought out, such as the type of support, excitation frequency, and speed of the harmonic load [15][16][17]. Minh et al [16] studied experimentally the vibration characteristics of cantilever sandwich beams and panels under the harmonic force applied at the free edge based on the response history of the accelerometer signal and displacement signal.…”
Section: Introductionmentioning
confidence: 99%
“…The results concluded that experiments should be conducted with a load cell to measure the harmonic force and the fundamental frequency of the live load. Makki [17] studied analytically the responses of continuous deep beams under harmonic loading using Timoshenko beam theory and dynamic equations and then verified the results with a numerical analysis using ANSYS APDL V.15.0 software. It was concluded that minimizing the shear span of the beam-todepth ratio decreased the deflection wave amplitudes and that replacement provided more ductility due to the rubber's elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that, concrete is a brittle material that cannot resist dynamic loads. Enhancing dynamic properties of concrete investigated by researchers using different ways like adding steel fibers or rubbers or even both [1][2][3][4]. Since rubber is not a biodegradable material and for its low cost against the high cost of steel fiber and for sustainability, it can be used as a percentage replacement from mix aggregate.…”
Section: Introductionmentioning
confidence: 99%